Characterization of the effects of the anger in pitchers of baseball category 13-15 years (Revista científica Olimpia, 2015)
In Psychology, investigations applied to sport show a numerous list of scientists who have dedicated their efforts to the emotional control of athletes; however, the topic of annoyance and its influence, as well as its role as catalyst for more intense emotions has not been sufficiently investigated. This article shows the results of a diagnosis of the causes of annoyance emergence, expressions and physiological changes of the phenomenon in teenage baseball pitchers, as well as some implications in the sports results of the team (13-15 years category) of Santa Rita in Jiguaní municipality, Granma province.
Keywords: anger; pitchers; baseball; emotional control